Effect of copper addition on stability of bioceramics based on biogenic hydroxyapatite and sodium borosilicate glass in physiological solutions - Sych, O.E.; Boshytska, N.V.; Kuda, O.A.; Demyda , M.B.; Pinchuk, N.D.; Тоmila Т.V.; Bataiev, Yu.M.; Bataiev, N.N.; Protsenko , L.S.; Budilina, O.M. (Reports of the National Academy of Sciences of Ukraine, 2020)
The influence of copper as a modified additive on the in vitro properties of bioceramics based on biogenic hydroxyapatite and sodium borosilicate glass is investigated. It is established that the introduction of copper to the bioceramics composition in an amount of 0.5—2.0 wt. % reduces the pH level of saline and decreases the dissolution rate of materials in a simulated body fluid, which allows one to regulate the resorption within the necessary limits for the individual characteristics of patients. The study of the stability of bioceramics in distilled water, saline, and Ringer’s solution showed that bioceramics most actively interacts with a NaCl solution. The amount of calcium and phosphorus that released into the solution depends on the duration of the experiment and the amount of a modified additive. Copper was fixed only in the NaCl solution with a modified additive content of <img class="mwe-math-fallback-image-inline" style="height: 2.176ex; vertical-align: -0.505ex; width: 1.808ex;" src="https://wikimedia.org/api/rest_v1/media/math/render/svg/82e7d18b196b7b9060634a9c96a324be85704341" alt=""> 1.0 wt. %. In addition, according to the EPR method, it is shown that increasing the amount of copper in bioceramics leads to a displacement of the EPR lines toward higher energies, and the magnitude of the displacement is described in the framework of the Night shift theory for ferromagnets.